Enabling water-free PEDOT as hole selective layer in lead-free tin perovskite solar cells. Issue 24 (11th November 2022) - Di Girolamo, Diego; Aktas, Ece; Ponti, Corinna; Pascual, Jorge; Li, Guixiang; Li, Meng; Nasti, Giuseppe; Alharthi, Fahad; Mura, Francesco; Abate, Antonio
Abstract : A thin layer of Al2 O3 nanoparticles has been deposited on top of a water-free PEDOT layer to modify wettability for obtaining pinhole-free homogenous tin-based perovskite films, resulting in better device performance. Abstract : Metal halide perovskites are set to revolutionise photovoltaic energy harvesting owing to an unmatched combination of high efficiency and low fabrication costs. However, to improve the sustainability of this technology, replacing lead with less toxic tin is highly desired. Tin halide perovskites are approaching 15% in power conversion efficiency (PCE), mainly employing PEDOT:PSS as a hole-selective layer. Unfortunately, PEDOT:PSS is processed from an aqueous solution, which is hardly compatible with the strict anoxic requirements for processing tin halide perovskites due to tin's instability to oxidation. Here, we present a water-free PEDOT formulation for developing tin-based lead-free perovskite solar cells. We show that the main difference between the PCE of devices made from aqueous and water-free PEDOT is due to the marked hydrophobicity of the latter, which complicates the perovskite deposition. By modifying the surface of water-free PEDOT with a thin Al2 O3 interlayer, we could achieve good perovskite morphology that enabled perovskite solar cells with a PCE of 7.5%.